1977
DOI: 10.1530/jrf.0.0490077
|View full text |Cite
|
Sign up to set email alerts
|

Fluid reabsorption in the isolated duct of the rat cauda epididymidis

Abstract: A technique is described fro measurement of rate of fluid reabsorption in a segment of the rat cauda epididymidis in vitro. The basal rate was 2-63 +/- 0-22 mul/cm2/30 min and was dependent on temperature and inhibited by 2,4-dinitrophenol, suggesting that fluid reabsorption is an energy-dependent process. About 50% of the fluid reabsorption was dependent on intraluminal sodium ions. This Na+-dependent component was inhibited by addition of amiloride to the intraluminal fluid and ouabain to the peritubular flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Sodium-potassium activated ATPase appears to be involved in the sodium-dependent reabsorption of water in the isolated rat cauda epididymidis [13]; the activity of this enzyme may be androgen dependent [ 141. The elevated chloride concentrations in the caput and distal cauda after eight weeks of CA treatment would be consistent with the presence of an androgen-dependent sodium pump in the epididymal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-potassium activated ATPase appears to be involved in the sodium-dependent reabsorption of water in the isolated rat cauda epididymidis [13]; the activity of this enzyme may be androgen dependent [ 141. The elevated chloride concentrations in the caput and distal cauda after eight weeks of CA treatment would be consistent with the presence of an androgen-dependent sodium pump in the epididymal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…), which would be expected if water moves passively across the epididymis secondary to a net transepithelial transport of sodium ions (Wong & Yeung, 1977, 1978. Concentration of Na+ in perfusate (mmol/1) Fig.…”
mentioning
confidence: 97%
“…
In the cauda epididymidis, sodium chloride is reabsorbed isotonically with water and potassium is secreted into the ductal lumen (Wong & Yeung, 1977, 1978; these transport processes seem to have many characteristics typical of the processes occurring in the distal tubule of the kidney. Apart from electrolyte and water transport, proteins are also secreted into the ductal lumen.
…”
mentioning
confidence: 99%
“…The mechanism of fluid reabsorption has been studied in isolated duct of rat epididymis in vitro. It was found that 50 % of the fluid reabsorption is secondary to an active transepithelial transport of sodium ions (4,5). Furthermore this process, like many epididymal functions, is abolished by castration, indicating that the fluid reabsorption process is dependent upon the presence of circulating androgens (6).…”
mentioning
confidence: 99%